STRATEGI PEMASARAN SOSIAL YAYASAN SETARA MELALUI AKTIVASI MEDIA SOSIAL, SOSIALISASI ORANG TUA, REKRUTMEN RELAWAN, MAIN EVENT, DAN PENDAMPINGAN ANAK - Shafhah Meiska; Joyo Nur Suryanto Gon (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Child protection in Indonesia remains a serious issue due to low public awareness. YayasanSetara addresses this through social marketing programs to increase visibility and communityparticipation. This report highlights the author’s roles in Public Relations and Sponsorship &Partnership in implementing programs such as outreach, educational media distribution,community engagement, and the Setara Youth Movement event, using an Integrated MarketingCommunication (IMC) approach. The results show increased organizational visibility andcommunity involvement, indicating that integrated communication strategies effectivelyenhance awareness and participation in child protection efforts.